ANALISIS KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD (STUDI KASUS PT XYZ BERGERAK DI BIDANG TELEKOMUNIKASI) - Widyastuti, Indira Tyas; Indriana, Indriana; Umar, Abdullah; Bawono, Adhi (STIKS Tarakanita, 2017)
Balance Scorecard is a management method which can be used by the company to measure organizational performance and strategy implementation effectively. The objective of the research is to measure the companyâ€™s performance using four perspective of Balanced Scorecard: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This research used the combination of historical data analysis, Balanced Scorecard analysis, and Strategic Management Analysis. The conclusion of the research is that Balanced Scorecard method is proven to measure companyâ€™s performance in more comprehensive way, better than traditional method that only measure financial factor. Also, the company can map the strength and weakness to improve its performance.Â